Antioxidant responses and plasma biochemical characteristics in the freshwater rainbow trout, Oncorhynchus mykiss, after acute exposure to the fungicide propiconazole - Z.-H. Li; V. Zlabek; J. Velíšek; R. Grabic; J. Machová; J. Kolařová; P. Li; T. Randák (Czech Journal of Animal Science, 2011)
In this study, the toxic effects of PCZ, a triazole fungicide present in aquatic environment, were studied in rainbow trout, Oncorhynchus mykiss, by an acute toxicity test. Compared to the control group, fish exposed to PCZ (96-h-LC50, 5.04 mg/l) showed significantly higher (P < 0.05) plasma NH3 and GLU concentration and the activities of plasma enzymes including CK, ALT, AST, LDH, but the TP content was not significantly different (P > 0.05). The oxidative stress indices (levels of LPO and CP) of brain and muscle in the experimental group were higher compared to the control group, especially for a significant change (P < 0.05) in the brain. SOD, CAT, GPx and GR activity in the brain of experimental groups was significantly lower (P < 0.05), however, an opposite tendency was found out in muscle. In addition, there are significant correlations between TBARS and CAT, TBARS and GPx, CP, and CAT, GR, and GPx in the fish brain. Thus, PCZ exposure changed the oxidative stress indices and plasma characteristics, and these changes may be used as potential bioindicators of the exposure and effect of PCZ in the controlled experiment. The use in monitoring of PCZ exposure under natural field conditions is possible, but it needs further investigations.